2021
DOI: 10.1242/jcs.259012
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced changes of α-catenin conformation stabilize vascular junctions independently of vinculin

Abstract: Cadherin-mediated cell adhesion requires anchoring via the β-catenin-α-catenin complex to the actin cytoskeleton, yet, α-catenin binds F-actin only weakly. A covalent fusion of VE-cadherin to α-catenin enhances actin anchorage in endothelial cells and strongly stabilizes endothelial junctions in vivo, blocking inflammatory responses. Here, we have analyzed the underlying mechanism. We found that VE-cadherin-α-catenin constitutively recruits the actin adaptor vinculin. However, removal of the vinculin binding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The interaction of the VE-Cadherin -Catenin complex with the actin cytoskeleton stabilizes the AJs and maintains endothelial monolayer integrity (19)(20)(21). Tension on the VE-Cadherin complex results in unfolding of α-Catenin, which enhances its Actinbinding affinity and exposes a cryptic binding site for Vinculin (22)(23)(24)(25)(26)(27)(28). The Vinculin -α-Catenin interaction drives α-Catenin-mediated mechanotransduction and preserves junctional integrity during force-dependent remodelling in cultured endothelial and epithelial cells (22,25,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the VE-Cadherin -Catenin complex with the actin cytoskeleton stabilizes the AJs and maintains endothelial monolayer integrity (19)(20)(21). Tension on the VE-Cadherin complex results in unfolding of α-Catenin, which enhances its Actinbinding affinity and exposes a cryptic binding site for Vinculin (22)(23)(24)(25)(26)(27)(28). The Vinculin -α-Catenin interaction drives α-Catenin-mediated mechanotransduction and preserves junctional integrity during force-dependent remodelling in cultured endothelial and epithelial cells (22,25,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Tension on the VE–cadherin complex results in unfolding of α-catenin, which enhances its actin-binding affinity and exposes a cryptic binding site for vinculin ( 16 , 22 , 23 , 24 , 25 , 26 , 27 ). The vinculin–α-catenin interaction drives α-catenin-mediated mechanotransduction and preserves junctional integrity during force-dependent remodelling in cultured endothelial and epithelial cells ( 22 , 25 , 28 , 29 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…We employed a Vinculin biosensor to assay the force distribution next to the contracting cells ( Kong et al, 2019 ) and obtained an estimation for the reach of the pulling force by the contracting cell. This biosensor is based on the force-dependent conformational change of alpha-Catenin (alpha-Cat), a component of adherence junctions and binding partner of E-Cad ( Choi et al, 2012 ; Rangarajan and Izard, 2012 ; Yao et al, 2014 ; Duong et al, 2021 ). In the closed state, the central mechanosensitive modulatory (M) domain of alpha-Cat is inaccessible to the D1 domain of Vinculin.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we probed for tension-sensitive changes in the conformation of α-catenin at head-on versus side-side contacts. Mechanical tension opens the central M-domain of α-catenin 25 and also unfolds the autoinhibited alpha1 helix in the F-actin-binding site (ABD) 22 ; these conformational changes are detectable with the α18 monoclonal 25 and VD7 polyclonal antibodies 26 , respectively (Fig 4E). Consistently, we found that staining for both α18 and VD7, corrected for total α-catenin, was more intense in AJ at head-on contacts compared with side-to-side contacts (Fig 4F, G).…”
Section: Resultsmentioning
confidence: 99%
“…Rat monoclonal antibody against α-catenin M-domain (α18) was kindly provided by Dr. A. Nagafuchi (Kumamoto University, Japan). Rabbit polyclonal antibody against a-catenin ABD (VD7) has been described before 26 .…”
Section: Star Methodsmentioning
confidence: 99%